2015
DOI: 10.1016/j.ymgme.2015.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Intrathecal 2-hydroxypropyl-beta-cyclodextrin in a single patient with Niemann–Pick C1

Abstract: Niemann-Pick C, Type 1 (NPC1) is a progressive autosomal recessive neurologic disease caused by defective intracellular cholesterol and lipid trafficking. There are currently no United States Food and Drug Administration approved treatments for NPC1. We undertook a study evaluating the safety, efficacy, and biomarker response of intrathecal 2-hydroxypropyl-β-cyclodextrin (HP-β-CD) in a 12-year old subject with mildly symptomatic NPC. The subject received 200mg intrathecal HP-β-CD administered biweekly via lumb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(55 citation statements)
references
References 28 publications
3
50
0
2
Order By: Relevance
“…This study also reported an increase in 24-OH cholesterol, a biomarker of cholesterol redistribution in CNS. On the other hand, an AE was associated to HP-β-CD administration, the well-known hearing loss to high frequency [44].…”
Section: Experience In Humans: Efficacy Of the Intrathecal Administramentioning
confidence: 99%
See 2 more Smart Citations
“…This study also reported an increase in 24-OH cholesterol, a biomarker of cholesterol redistribution in CNS. On the other hand, an AE was associated to HP-β-CD administration, the well-known hearing loss to high frequency [44].…”
Section: Experience In Humans: Efficacy Of the Intrathecal Administramentioning
confidence: 99%
“…Of the 17 AEs reported, 6 were related to the route of administration, specifically with the IT and ICV routes and 10 of them could be attributed by HP-β-CD. Six AEs associated to the route were: CNS bleed related to insertion of the Ommaya reservoir system in a patient treated with ICV HP-β-CD led to ICV administration suspended [34]; post lumbar puncture headache and vomiting resolved with switching a Whitacre spinal needles [41][42][43]; post lumbar puncture pain, headache, nausea, and vomiting resolved with symptomatic and postural treatment [44]; seizures with fever resolved without changes in treatment [40] and aspiration pneumonia; febrile syndrome; and candidiasis resolved with antibiotic and antifungal treatment [49].…”
Section: Experience In Humans: Potential Toxicities Of the Different mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, intrathecal infusion of HP-β-CyD to NPC patients has been performed to reduce the risk of adverse events in lung. 54) Meanwhile, Kondo et al 55) reported effects of hydroxyalkylated β-CyDs with different cholesterol-solubilizing abilities, such as 2-hydroxyethyl-β-CyD (HE-β-CyD) and 2-hydroxybutyl-β-CyD (HB-β-CyD). Based on the results regarding cholesterol solubilizing potential, attenuating the effects against NPC abnormalities and cytotoxicity induction, HB-β-CyD may be superior in terms of safety and efficacy in Npc1 null cells compared with HE-β-CyD and HB-β-CyD.…”
Section: Hp-β-cyd For Treatment Of Niemann-pick Disease Type C (Npc)mentioning
confidence: 99%
“…Intravenous HPBCD was trialled on two NP-C patients [Matsuo et al 2013] and had little or no effect in controlling or delaying neurological symptoms, although it resulted in improvement of liver size and function. A 12-year old patient with NPC1 was recently given HPBCD intrathecally every 2 weeks and response was assessed after 27 injections [Maarup et al 2015]. The NP-C severity scale score improved over 18 months, with all neurological functions remaining stable and a 1-point improvement shown in eye movements.…”
Section: -H Y D R O X Y P R O P Y L -B E T a -C Y C L O D E X T R I Nmentioning
confidence: 99%